An open-label study of effects of acupuncture on chronic fatigue syndrome and idiopathic chronic fatigue: study protocol for a randomized controlled trial - Kim, Jung-Eun (BioMed Central, 2013)
BACKGROUND: Even though chronic fatigue syndrome and idiopathic chronic fatigue are quite common, there are no clearly known causes. Most treatments are therefore symptomatic in nature, and chronic fatigue syndrome and idiopathic chronic fatigue patients are highly interested in using oriental medicine or complementary and alternative medicine treatment. Acupuncture, one of the major treatments used in oriental medicine, is effective in treating various diseases. This study will attempt to analyze the effectiveness and safety of acupuncture in the treatment of chronic fatigue by comparing the two treatment groups (body acupuncture, Sa-am acupuncture) and the control group (usual care). METHODS/DESIGN: This study consists of a four-center, three-arm, randomized, controlled, and open-label trial. One hundred and fifty participants are randomly divided into treatment groups A and B and a control group. The treatment groups will receive acupuncture treatments either two or three times per week for a total of 10 sessions over a period of 4 weeks. The control group will not receive acupuncture treatments and will continue their usual care during this period. The primary outcome variable is the Fatigue Severity Scale, which will be utilized 5 weeks after randomization. Secondary outcome variables are the Fatigue Severity Scale at 13 weeks, a short form of the Stress Response Inventory, the Beck Depression Inventory, the Numeric Rating Scale, and the EuroQol-5 Dimension at 5 and 13 weeks after randomization. DISCUSSION: This study will provide evidence with high external validity on the effectiveness and safety of acupuncture as a treatment for chronic fatigue syndrome and idiopathic chronic fatigue. TRIAL REGISTRATION: Clinical Research Information Service KCT0000508